Perencanaan Pendidikan dalam Upaya Meningkatkan Kompetensi Guru - Gusnita, Fitria; Annisa, Mella; Triana, Mamy; Asmendri; Sari, Milya (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This study aims to identify the factors that influence educational planning in improving teacher competence in Indonesia, as well as addressing the challenges that arise in its implementation. The method used is a qualitative study with in-depth interviews with school principals, teachers, and education officials in several regions. The main findings of this study indicate that effective educational planning must include the development of teacher competence through ongoing training, particularly in utilizing technology in the teaching and learning process. In addition, the planning should also focus on developing students' character and social skills. However, the main challenge faced is the lack of support from the government and the community, which hinders the success of professional development programs for teachers. This study recommends the need for more focused, collaborative, and sustainable educational planning among various parties, as well as better synergy between education policies and their implementation in the field to create a more optimal learning environment.sustainable educational planning is necessary to improve teacher competencies.